Internalisasi Nilai-Nilai Pendidikan Multikultural dalam Pembelajaan Sejarah Kebudayaan Islam Prespektif Skinner - Nikmah, Choirun; Fauzi, Ahmad (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
This research focuses on (1) the process of internalizing multicultural education values in learning Islamic Culture History class VII at MTs Al Mahrusiyah Lirboyo Kediri, (2) the perspective of Skinner's operant conditioning theory on the internalization of multicultural education values in learning Islamic Culture History class VII at MTs Al Mahrusiyah Lirboyo Kediri. The research approach used is a descriptive qualitative approach. Data is collected in the form of words and images, not in the form of numbers. The data is collected through interviews, field notes, records, photos, personal documents, etc. Primary data is obtained by researchers as a source of information from the principal, Islamic cultural history subject teacher, Deputy Head of Student Affairs, Deputy Head of Curriculum, and seventh-grade students of MTs Al Mahrusiyah. The results showed that the teacher carried out the process of internalizing multicultural education values in learning Islamic cultural history by emulating the story of the prophet Muhammad SAW contained in the SKI material and the following steps: (1) determining multicultural values according to SKI learning indicators, (2) selecting materials that contain multicultural values, (3) conducting the learning process with the small group discussion method, and (4) evaluation. Other results show several things contradict the application of Skinner's operant conditioning theory, including (1) Skinner's operant conditioning theory shows that changing students' behavior only requires programmed learning. In contrast, the findings in the field show that in addition to programmed learning, there is also an environmental adjustment. The pesantren environment is the main supporting factor, and (2) Skinner's operant conditioning theory views behavior change as a learning process that does not require another process. At the same time, field findings show that students must experience the learning process first so that their behavior changes. In other words, learning is a process that mediates behavior.